Improving the TAMI for use with athletes - Madan, C. R.; Singhal, A. (Journal of Sports Sciences, 2014)
Athletes have been shown to have greater movement imagery abilities than non-athletes. However, since these differences were observed using questionnaires where participants subjectively judged the vividness of performing imagined movements, it is possible that responses could be biased by other factors such as social desirability. One possible solution is to use an objective test, such as the Test of Ability in Movement Imagery (TAMI; Madan, C. R., & Singhal, A. (2013). Introducing TAMI: An objective test of ability in movement imagery. Journal of Motor Behavior, 45, 153-166.). Unfortunately, young adults perform relatively well on the TAMI, leaving little room for statistical sensitivity in observing higher scores. Here we propose an alternate scoring method for the TAMI that resolves this limitation by weighing items according to their difficulty. We apply this scoring method to existing data and show that this improves the TAMI`s selectivity to measuring ability in movement imagery, rather than related imagery processes. Thus, we have successfully improved the TAMI to be more suited for use with athletic populations.